Using Digital Marketing to Develop Marketing Strategy for Fish Farmer Group Products in Jehem Village - Vidya Shania Devi; Kadek Devi Kalfika Anggria Wardani; Dewa Ayu Putu Adhiya Garini Putri (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Fish Farmer Group